Formação Docente Digital (FDD) e o uso do chromebook: uma pesquisa-ação em uma escola pública do município de Fortaleza-CE - Azevedo, Igor Márcio do Nascimento (2025)
Continuing education of teachers is a very important theme within the act of teaching and being a teacher, mainly because it ensures that, throughout their training, teachers can improve themselves with new knowledge and practices that society demands. Returning to the pandemic context in the city of Fortaleza, it can be observed that even teachers who had access to digital technologies had great difficulty developing digital skills that would prepare them to use them in their pedagogical practice. In this sense, this dissertation aimed to investigate how continuing digital education (FDD) contributed to pedagogical practice and the uses of digital technologies by teachers at a municipal public school integrated with the Google innovation room. The research proposes to have a qualitative approach, of an applied nature. It is considered descriptive and with regard to data collection procedures and instruments, a case study and action research. Being made through literature review, a field research with Collaborative Interdisciplinary Training (FIC) with students from different courses at the Federal University of Ceará so that they can contribute to FDD in a school in the municipal public network of Fortaleza-CE. The research subjects were fourteen teachers from a municipal school in Fortaleza, from August 2024 to December 2024. The data collection instruments were field diaries, questionnaires, in addition to participant observation. In the first stage of the research, we carried out interdisciplinary training called FIC, with the aim of contributing to the development of digital and academic skills for several undergraduate scholarship students, who would later be part of the second part of the research, the FDD, helping to develop the digital inclusion of teachers at a public school in the city of Fortaleza-CE. The results point to the need for continued training focused on the use of digital technology in teaching practice, as many teachers stated that they did not participate in any training that would help them develop digital skills in relation to the basic handling of the Chromebook computing tool; the time factor and structured material were identified as determining factors in understanding the processes of digital culture; insecurity in handling technologies, especially digital immigrant teachers. The analysis of the data obtained allowed us to affirm that there was a positive contribution in relation to improving the use of the Chromebook and digital inclusion in a more practical way during the FDD. Furthermore, we highlight aspects such as: on-site training, use of the innovation room for continued teacher training, as this is generally thought to be used for student learning, as teachers stated that they began to use this tool in a safer and more targeted way in their pedagogical work, even generating greater optimization of time and organization in pedagogical activities.